2003
DOI: 10.1677/erc.0.0100591
|View full text |Cite
|
Sign up to set email alerts
|

Two somatic TSH receptor mutations in a patient with toxic metastasising follicular thyroid carcinoma and non-functional lung metastases.

Abstract: In a 59-year-old patient, thyroid follicular cancer was diagnosed in two right-sided toxic thyroid nodules, which had presented clinically as unilateral thyroid autonomy. In addition, the patient had histologically proven lung metastases of thyroid cancer; however, these failed to exhibit iodine uptake and were resistant to radioiodine treatment. The functional activity of the thyroid nodules prompted us to screen for TSH receptor (TSHR) mutations, and the histological diagnosis of follicular carcinoma led us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 26 publications
2
35
0
1
Order By: Relevance
“…Mutations in the phosphatase and tensin homologue suppressor gene and the phosphatidylinositol 3-kinase pathway may be an important factor in the development of more aggressive thyroid cancers and may be more common in follicular cancer [21]. Other factors that have been implicated in the pathogenesis of follicular thyroid cancer include gene mutations in p53, c-myc, c-fos, and the thyrotropin (TSH) receptor [22,23].…”
Section: Pathogenesismentioning
confidence: 99%
“…Mutations in the phosphatase and tensin homologue suppressor gene and the phosphatidylinositol 3-kinase pathway may be an important factor in the development of more aggressive thyroid cancers and may be more common in follicular cancer [21]. Other factors that have been implicated in the pathogenesis of follicular thyroid cancer include gene mutations in p53, c-myc, c-fos, and the thyrotropin (TSH) receptor [22,23].…”
Section: Pathogenesismentioning
confidence: 99%
“…The remaining two mutations, Asp-632<Tyr (S8a) and Asp-632<His (S8b), have both been previously reported at human codon locus 633 in human hyperfunctioning adenomas/nodules and thyroid carcinomas as somatic, heterozygous mutations (Kosugi et al 1994, Porcellini et al 1994, Van Sande et al 1995, Russo et al 1996, Parma et al 1997, Trulzsch et al 2001, Fuhrer et al 2003 but neither have been reported in FH. Only one cat with the S8a or S8b mutation had a concurrent blood sample: DNA from this blood sample did not harbour either mutation, and neither mutation was detected in blood from non-hyperthyroid cats.…”
Section: Tablementioning
confidence: 99%
“…Five of the 10 mis-sense mutations have previously been identified in human hyperthyroidism (Kosugi et al 1994, Porcellini et al 1994, Van Sande et al 1995, De Roux et al 1996, Russo et al 1996, Spambalg et al 1996, Tonacchera et al 1996, 2000, Duprez et al 1997a, Parma et al 1997, Lavard et al 1999, Mircescu et al 2000, Trulzsch et al 2001, Vanvooren et al 2002, Fuhrer et al 2003, Georgopoulos et al 2003.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…12 Polyethylene glycol-purified PCR products were sequenced using BigDye terminator sequencing chemistry (Applied Biosystems, Carlsbad, CA), and sequence analysis was performed on the Genetic Analyzer ABI 377 (Applied Biosystems) as previously described. 13 Positive controls were cDNA from plasmids carrying the H1047R (provided by Dr. Bert Vogelstein, Johns Hopkins University Medical Institutions, Baltimore, MD) and the PAX8/PPAR␥ rearrangement (provided by Dr. Todd Kroll, University of Chicago Medical Center, Chicago, IL). 14 The H-RASV12 mutation was generated in human cDNA (from NT tissue) using the Stratagene Quick-Change site-directed mutagenesis kit according to the manufacture's description and the following primers: RASV12F 5=-AAGCTGGTGGTG-GTGGGCGCCGTCGGTGTGGGCAA-3= and RASV12R 5=-TTGCCCACACCGACGGCGCCCACCACCACCAGCTT-3=.…”
Section: Mutational Screening and Sequencing Analysismentioning
confidence: 99%